Different expression of NF-kB and endometrial implant width in the administration of red fruit (Pandanus conoideus Lam) and leuprolide - Raudatul Hikmah; Hendy Hendarto; Widjiati Widjiati (Majalah Obstetri dan Ginekologi, 2022)
HIGHLIGHTS 1. Endometriosis treatment remains controversial, whether it should be managed with hormonal modulation and/or surgical removal of the lesion.2. NF-kB becomes potential therapeutic target as it has constitutive activation in peritoneal endometriosis.3. It has been recognized that NF-kB expression decreases when red fruit extract is given.4. Effect of red fruit extract, compared to leuprolide, a widely used treatment for endometriosis, on NF-kB expression was examined.5. NF-kB was significantly lower in endometriotic group receiving red fruit extract than in group receiving leuprolide.   ABSTRACT Objectives: This study aimed to prove the effect of different administration of red fruit (Pandanus conoideus Lam) extract and leuprolide on the expression of NF-kB and endometrial implant width in mouse models of endometriosis. Materials and Methods: This study used completely randomized design with pre-post separated sample. The sample size was 36 female mice (Mus muculus), which were divided into 3 groups randomly. They were given with cyclosporine A, estrogen and endometrial tissue to form endometriosis model. Results: The mean expression of NF-kBin in treatment group receiving leuprolide (4.13 + 0.70) and red fruit (2.70 + 1.08) were significantly lower than that in control group (6.94 + 1.007). Whereas, in treatment group receiving red fruit (2.70 + 1.08), it was significantly lower than in those receiving leuprolide (4.13 + 0.70). Mean endometrial implant width in treatment group receiving leuprolide (13.62 + 3.21) and red fruit (8.93 + 2.74) were significantly lower than that in control group (28.89 + 8.28). Whereas, in treatment group receiving leuprolide (13.62 + 3.21), it was not significantly higher than in those receiving red fruit (8.93 + 2.74). Conclusion: The expression of NF-kB was significantly lower after the administration of red fruit than leuprolide. The width of endometrial implant was not significantly lower after the administration of red fruit than after the administration of leuprolide.